Psychological distress and physiological markers: differences comparison in first division football players - Naji, F. L.; Kamalden, T. F. T.; Amri, S. (International Journal of Human Movement and Sports Sciences, 2020)
This study aimed to determine the level of stress as measured through different stress measurement methods (DASS questionnaire, SIgA, pulse rate and oxygen saturation). The highest scores for depression, anxiety, stress, pulse rate were before the competition (M=8.365, SD=2.733), (M=8.689, SD=3.962), (M=10.068, SD=3.094), (M=63.27, SD=5.008) respectively. While for salivary IgA and oxygen saturation, the highest score was at resting time (M=112.147, SD=14.431), (M=98.3, SD=1.893) respectively. Descriptive method was used for data collection. Participants were 74 football players of all the first division clubs in Karbala, Iraq, aged between 18-22 years old. Depression, anxiety and stress were measured at three different time points (resting time, before the training, before the competition), while salivary IgA, pulse rate, and oxygen saturation measurement were measured through five different time points (resting time, before the training, after the training, before the competition, after the competition). It can be concluded that the combination of psychological distress and physiological markers can provide accurate measurements of stress.